Caveolin 1 mRNA is overexpressed in malignant renal tissue and might serve as a novel diagnostic marker for renal cancer. (April 2011) - Waalkes, Sandra; Eggers, Hendrik; Blasig, Hanna; Atschekzei, Faranaz; Kramer, Mario W; Hennenlotter, Jöörg; Träänkenschuh, Wolfgang; Stenzl, Arnulf; Serth, Jüürgen; Schrader, Andres J; Kuczyk, Markus A; Merseburger, Axel S
Background & aim: Caveolae play a significant role in disease phenotypes, such as cancer, diabetes, bladder dysfunction and muscular dystrophy. The aim of this study was to elucidate the expression of caveolin (CAV)1 in the development of renal cell cancer (RCC) and to determine a possible prognostic relevance for optimal clinical management.Material & methods: 109 RCC and 81 corresponding normal tissue specimens from the same kidney were collected from patients undergoing surgery for renal tumors and subjected to total RNA extraction. Quantification of CAV1 mRNA expression was performed using real-time reverse transcription PCR with three endogenous controls for renal proximal tubular epithelial cells and the ΔΔΔΔCt method for calculation of relative quantities. Expression levels were correlated to clinical variables.Results: Tissue-specific mean CAV1 expression was significantly increased in RCC compared with normal renal tissue (p = 0.0003; paired Wilcoxon rank sum test). CAV1 expression was increased 1.9-fold in clear cell RCC compared with papillary RCC (p = 1.48 ×× 10 ––7 ; unpaired Wilcoxon rank sum test). Patients with advanced disease had higher CAV1 expression when compared with organ-confined disease (p = 0.019; unpaired Wilcoxon rank sum test). Moreover, mean tissue-specific CAV1 expression was increased in patients with distant metastasis at the time of diagnosis compared with patients without metastasis (p = 0.0058; unpaired Wilcoxon rank sum test).Conclusion: To our knowledge, this is the first study to show that CAV1 mRNA expression, using quantitative real-time PCR, is significantly higher in RCC compared with normal renal tissue and increases with tumor stage. CAV1 mRNA expression might serve as a candidate biomarker for objective prognosis indicating RCC aggressiveness. Our data encourage further investigations to determine the role of CAV1 in RCC.